The Effect of Number Maze Media on the Beginning Arithmetic Ability of 5-6 Year Old Children at RA Perwanida 3 Palembang - Melani Firdha Maharani; Amir Hamzah; Tutut Handayani; Leny Marlina4 (Jurnal CARE (Children Advisory Research and Education), 2026)
Cognitive development describes how a child's mind functions and evolves, enabling the development of thinking skills. The use of maze-based learning media can alleviate boredom during the learning process due to its interactive nature and the engaging way the material is presented to children. The objective of this study was to determine the effect of "number maze" media on the early numeracy skills of children aged 5–6 years at RA Perwanida 3 Palembang. This study employed a quantitative experimental method. The population consisted of 51 children in Group B at RA Perwanida 3 Palembang, with a sample size of 17 children. Data collection techniques included observation, testing, and documentation. Data analysis involved several tests: validity, reliability, normality, homogeneity, and hypothesis testing. The hypothesis test was conducted using the t-test in SPSS for Windows (version 30), yielding a significance value (2-tailed) of 0.001 (p < 0.05). Thus, the significance level was below 0.05. It can be concluded that number maze media affects the early numeracy skills of children aged 5–6 years at RA Perwanida 3 Palembang.